2016
DOI: 10.1145/2957750
|View full text |Cite
|
Sign up to set email alerts
|

When Game Becomes Life

Abstract: Online gaming franchises such as World of Tanks, Defense of the Ancients, and StarCraft have attracted hundreds of millions of users who, apart from playing the game, also socialize with each other through gaming and viewing gamecasts. As a form of User Generated Content (UGC), gamecasts play an important role in user entertainment and gamer education. They deserve the attention of both industrial partners and the academic communities, corresponding to the large amount of revenue involved and the interesting r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 37 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…Nakandala et al (2017) explored social media discourses about digital entertainment with an emphasis on gender, pointing to a significant objectification against women. Jia et al (2016) found that community-maintained replay-based sites about gaming work as important outlets for discussing and appreciating group strategies related to games. Finally, Reitman et al (2020) directed a literature review about esports highlighting the importance of community factors in player's experiences with video games.…”
Section: Social Interactions Via Gamesmentioning
confidence: 99%
“…Nakandala et al (2017) explored social media discourses about digital entertainment with an emphasis on gender, pointing to a significant objectification against women. Jia et al (2016) found that community-maintained replay-based sites about gaming work as important outlets for discussing and appreciating group strategies related to games. Finally, Reitman et al (2020) directed a literature review about esports highlighting the importance of community factors in player's experiences with video games.…”
Section: Social Interactions Via Gamesmentioning
confidence: 99%
“…helpers vs. power seekers) in participatory games can further shape community identity [69]. Thoughtfully designing for these roles is particularly important because streamers and viewers favor diferent relationship dynamics; content creators often focus on their individual skills, whereas viewers appreciate team dynamics [41]. Moderators enjoy a special role in the streaming community, and are highly valued by both streamers and viewers [69].…”
Section: Communitymentioning
confidence: 99%
“…A substantial number of these papers have their roots in the discipline of psychology, which has a long tradition of developing and using models to explain behavior [59,60,65]. The subdomains focused on the platform and the transmission are characterized by the use of more heterogeneous methods, although the former stands out for the inclusion of descriptive statistics and techniques for constructing graphs [87][88][89][90][91][92], and the latter for compiling information through application programming interfaces (APIs), both for Twitch [73,[93][94][95][96][97] and other platforms such as Douyu [98]. The collection of information through public APIs is spreading to other subdomains (Streamer [99] Riot Games API; Receiver [100] Twitch API; and Platform [87,89,91] Twitch API), opening up future research opportunities if simultaneous information about the streamer, receiver, and platform can be connected.…”
Section: The Domain Of Research On Video Game Live Streamingmentioning
confidence: 99%
“…The term Twitch features particularly strongly in the subdomain or specialization focused on analyzing platforms. In relation to this node, comparisons with other streaming platforms [88] have been carried out, subcultures of players and viewers have been identified [89], and shared patterns of media consumption and production have been analyzed, [52] as well as the similarities and differences with fastconsumed repositories [90] or with other types of "static" content distribution platforms such as YouTube and Netflix [91]. In addition, Twitch has served as a reference to analyze traffic patterns [92], examine its business model and impact on the video game industry [8], explore its potential in terms of marketing [109] and education [71], and study its content policies [119].…”
Section: Thematic Structure Of the Research Domainmentioning
confidence: 99%